Conflict Management Between Teachers and Boarding Students - Toha Hasan Anwar; Duwi Habsari Mutamimah; Muhammad Fahmi Maulana (Jurnal Paradigma, 2025)
Disciplinary violations committed by dormitory students, such as truancy and leaving the dormitory environment without permission, are a form of conflict that often occurs in the Islamic education environment. This study aims to analyze the conflict management strategies applied by teachers in handling disciplinary violations at MTs Filial Ma'arif Darul Ulum, Sidoharjo. This research covers how teachers respond to students who commit repeated violations and what strategies are used to resolve conflicts in an educational way. This study uses a qualitative approach with a case study method. Data collection techniques are carried out through observation, in-depth interviews, and documentation. The data analysis uses the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawn. The results of the study show that the handling of disciplinary violations at MTs Filial Ma'arif Darul Ulum is carried out through a combination of educational strategies, such as individual counseling, Islamic values approach, and restorative communication. Thomas & Kilmann's collaborative approach has proven to be relevant in building students' awareness and character. These results show the importance of developing SOP for handling discipline that is participatory and based on Islamic values to form a sustainable culture of discipline in the dormitory madrasah environment.